Multiple influences on cyanobacterial abundance and diversity in the Beijing-Tianjin-Hebei Economic Circle and nearby areas of China - Wei Wang; Hanjie Huang; Kangxu Zhao; Junping Lv; Xudong Liu; Shulian Xie; Jia Feng (Current Research in Microbial Sciences)
Abstracts: In recent years, there has been a marked increase in the frequency and duration of cyanobacterial blooms, which has attracted widespread attention from all sectors of society. However, the processes and pathways leading to the formation of cyanobacterial blooms are largely stochastic, and a targeted quantitative model incorporating multiple drivers is required. A series of fieldwork and analytical procedures were conducted on 11 lakes in Beijing-Tianjin-Hebei and neighboring regions. The objective of this research was to investigate the effects of location, climate, habitat, metabolism and biology on the abundance of cyanobacteria. The findings indicated that location factors exerted an indirect influence on cyanobacterial density, with a calculated effect size of −0.001. This observation is consistent with the documented prevalence of cyanobacterial bloom outbreaks, suggesting that cyanobacterial abundance is not directly associated with location. Furthermore, the water environment (0.35 indirect and −0.37 direct effects) and climatic conditions (−0.2 indirect and 0.16 direct effects) had significant direct and indirect effects on cyanobacterial cell densities. It was also determined that high nutrients and high temperatures remained the basis for promoting cyanobacterial blooms. It is noteworthy that the microbial community exerted a substantial inhibitory effect on the proliferation of the cyanobacterial community (1.13 direct inhibitory effect). It is hypothesized that the negative effect is derived from two primary sources: the competition for ecological niches by organisms exhibiting similarity, and the direct inhibitory effect of certain bacteria on the growth of cyanobacteria, a negative correlation between acidobacteriota, bacteroide and a variety of cyanobacteria was observed in our study. The effect of specific bacteria is found to be significantly negatively correlated with the prevalence of a wide range of cyanobacteria, which is consistent with the results of many extant studies. These extant studies indicate that the formation of cyanobacterial communities is primarily influenced by microorganisms in the environment. The results of this study will provide new and complementary evidence on the mechanisms of cyanobacterial bloom occurrence and development and the design of management strategies.